Progress and challenges of artificial intelligence in lung cancer clinical translation - Erjia Zhu; Amgad Muneer; Jianjun Zhang; Yang Xia; Xiaomeng Li; Caicun Zhou; John V. Heymach; Jia Wu; Xiuning Le (npj Precision Oncology)
Abstract Artificial intelligence (AI) algorithms, such as convolutional neural networks and transformers, have significantly impacted cancer care. For lung cancer, AI holds great potential in addressing smoking cessation, personalized screening, and imaging genomics. And these data could be incorporated to optimize treatment selection. This review highlights the transformative impact of AI in lung cancer management, discusses crucial barriers such as model bias and fairness, and outlines future directions for clinical application.